Linear or non-linear rheology in the Earth’s mantle: the prevalence of power-law creep in the postglacial isostatic readjustment of Laurentia - GASPERINI, PAOLO; DAL FORNO, GIULIO; BOSCHI, ENZO (Geophysical Journal International, 2004)
namics The great majority of postglacial rebound computations carried out during the last three decades assumed a purely linear rheological relation for the mantle. Experimental data on high-temperature creep deformation and modelling of other tectonic processes, however, might also support the existence of non-linear creep mechanisms. We addressed postglacial rebound in North America through an axially symmetric finite-element model with a composite (linear plus non-linear) mantle rheology. In such a formulation, the transition stress σ T governs the balance between linear and non-linear creep components, while the term σ B, added to the effective shear stress, accounts for the background (ambient) stress induced by convection and other tectonic processes. By varying σ T and σ B in the ranges 0–10 MPa and 0–5 MPa respectively, we found that composite models fit Relative Sea Level (RSL) variations at 29 North American sites better than the purely linear model. On the basis of the effective shear stress induced in the mantle by glacial forcing (1–3 MPa), our results indicate that power-law creep accounts for the majority of the strain rate.